A Dual‐Mode Infrared Asymmetric Photonic Structure for All‐Season Passive Radiative Cooling and Heating. (13th May 2022) - Ly, Kally Chein Sheng; Liu, Xianghui; Song, Xiaokun; Xiao, Chengyu; Wang, Pan; Zhou, Han; Fan, Tongxiang
Abstract: Radiative cooling is a revolutionary sustainable thermoregulating technology in favor to fight against global warming and urban heat island effects. However, the conventional designed high infrared emissive coolers do not function satisfactorily under atmospheric counter radiation (cloudy, humid, reduced sky access conditions) nor for all‐season thermal requirement (cooling and/or heating). Dual‐mode asymmetric photonic mirror (APM) consisted of silicon‐based diffractive gratings is presented, approaching an all‐season and all‐terrain optimized radiative thermal regulation. Based on the mechanism of asymmetric diffraction through high refractive index contrast mediums, the designed APM establishes an asymmetric radiative heat transfer channel for cooling and heating. An average infrared asymmetry of 20% for outgoing and incoming radiation is achieved by the fabricated APM. The remarkable cooling power of APM surpasses 80% over the standalone radiative cooler (RC) for counter radiation conditions. Under cloudy sky, the cooling‐APM achieves 8 ° C lower than RC standalone, while the heating‐APM 5.7 ° C higher, which presents prominent advantages over conventional coolers for different thermal management needs. The proposed dual‐mode infrared asymmetric photonic structure is promising to overcome shortcomings of conventional radiative cooling and offers breakthrough developments in future energy‐saving thermal management system. Abstract : A dual‐mode infrared asymmetric photonic mirror (APM) is proposed for all‐season and all‐weather passive radiative heating and cooling. The APM functions as heat channel with cooling function when upside down and heating function when side up. It is first successfully proved that the optical asymmetry brings breakthrough optimization for passive thermoregulation. Under counter atmospheric radiation, the cooling‐ and heating‐APMs achieve respectively 8 °C lower and 5.7 °C higher temperature than radiative cooler standalone. The proposed asymmetric photonic structure offers breakthrough developments in future energy‐saving radiative thermoregulating system.